Gene expression profiling to define the cell intrinsic role of the SKI proto-oncogene in hematopoiesis and myeloid neoplasms - Alistair M. Chalk; Brian J.J. Liddicoat; Carl R. Walkley; Sofie Singbrant (Genomics Data, 2014)
The proto-oncogene SKI is highly expressed in human myeloid leukemia and also in murine hematopoietic stem cells. However, its operative relevance in these cells remains elusive. We have over-expressed SKI to define its intrinsic role in hematopoiesis and myeloid neoplasms, which resulted in a robust competitive advantage upon transplantation, a complete dominance of the stem and progenitor compartments, and a marked enhancement of myeloid differentiation at the expense of other lineages. Accordingly, enforced expression of SKI induced gene signatures associated with hematopoietic stem cells and myeloid differentiation. Here we provide detailed experimental methods and analysis for the gene expression profiling described in our recently published study of Singbrant et al. (2014) in Haematologica. Our data sets (available at http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE39457) provide a resource for exploring the underlying molecular mechanisms of the involvement of the proto-oncogene SKI in hematopoietic stem cell function and development of myeloid neoplasms.